Hubungan Pendapatan Keluarga dan Pola Makan dengan Kejadian Gizi Kurang pada Anak Balita di Puskesmas Tawiri-Laha Ambon - Zasendy Rehena (MOLUCCAS HEALTH JOURNAL, 2020)
Malnutrition is a condition where a person is declared malnourished or his nutritional status is below the average standard. Based on data from the Tawiri-Laha Ambon Health Center, there are still many children under five who are malnourished. This study aims to determine the factors associated with the incidence of malnutrition in children under five at the Tawiri-Laha Health Center Ambon. This research uses descriptive analytic research design with cross sectional approach. The number of samples is 40 children aged 3-5 years. The sampling technique was using purposive sampling technique. The data were analyzed using the Chi-Square Test statistical test. The results showed that 1) there was a relationship between family income and malnutrition, p value = 0.000, 2) there was a relationship between diet and malnutrition, p value = 0.001. It was concluded that there was a relationship between family income and diet with the incidence of malnutrition in children under five at the Tawiri-Laha Health Center Ambon. It is hoped that the puskesmas will further improve health programs for the community.Keywords: Malnutrition, Income, DietÂ